Contributing Risk Factors for Substance Use Among Youth in Postconflict Liberia. (October 2018) - Petruzzi, Liana J.; Pullen, Samuel J.; Lange, Brittany C. L.; Parnarouskis, Lindsey; Dominguez, Silvia; Harris, Benjamin; Quiterio, Nicole; Lekpeh, Gondah; Manobah, Burgess; Henderson, David C.; Borba, Christina P. C.
Substance use is prevalent among youth in postconflict African countries and is associated with a number of public health problems such as poverty, child homelessness, and school truancy. This qualitative study explores the risk factors associated with substance use among Liberian youth from the perspective of public-school students. Nine focus groups were conducted with 72 Liberian public-school students (35 female, 37 male). Multiple risk factors for substance use among Liberian youth were identified through qualitative analysis, including emotional instability, gender, fear of academic failure, accessibility to substances within the school and community, poverty, and unintentional drug use. These findings are important to public health campaigns and postconflict recovery in Liberia, and may also inform prevention programs for substance use among Liberian youth.